The relevance of the tangible and intangible social impacts of tourism on selected South African communities. Issue 2 (2nd April 2016) - Scholtz, Marco; Slabbert, Elmarie
Abstract : Most tourism social impact studies emphasise tangible social impacts such as economic improvement. In developing countries such as South Africa, a small percentage of tangible benefits filter down to community level. This creates a problem as various studies revealed the importance of community support for the sustainability of the tourism industry. Therefore it was important to explore the role of both the tangible and the intangible social impacts of tourism. Communities with established tourism industries (Clarens, Soweto and Jeffreys Bay) formed part of the quantitative research. Through exploratory factor analyses, 31 social impact statements could be categorised into four tangible and two intangible impacts. The tangible factor Economic improvement obtained a low rating, meaning that it was not directly experienced by residents, while the intangible factor Community pride and upliftment obtained the highest rating among all factors. This, together with the fact that community members continue their support for the tourism industry, is a novel find, indicating the significant role of intangible social impacts in fostering community support. This finding shows the importance of incorporating intangible social impacts into tourism planning in developing countries. Contributions are made towards social impact research methodology and literature.